2012
DOI: 10.1097/fbp.0b013e3283566082
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin, a 5-HT2A receptor inverse agonist, reverses psychosis-like behaviors in a rodent model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by a progressive deterioration in cognitive functioning. Overall, 25-50% of patients with AD also show symptoms of psychosis including hallucinations and delusions. As all available antipsychotic drugs have a 'black-box' warning for use in these patients because of increased mortality, no appropriate treatment for psychotic symptoms in AD currently exists. In the present study, we examined whether selective antagonism of 5-HT(2A) serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Interestingly, applications of 5-HT 2 receptor inverse agonists have recently extended beyond schizophrenia. For example, in addition to psychosis associated with Parkinson’s disease [86], 5-HT 2 receptor inverse agonists are also being evaluated as treatments for psychosis related to Alzheimer’s disease [85] and for treatment of movement disorders related to Parkinson’s disease [87]. Overall, a better understanding of inverse agonism at 5-HT 2 receptor systems could have far-reaching implications for the development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, applications of 5-HT 2 receptor inverse agonists have recently extended beyond schizophrenia. For example, in addition to psychosis associated with Parkinson’s disease [86], 5-HT 2 receptor inverse agonists are also being evaluated as treatments for psychosis related to Alzheimer’s disease [85] and for treatment of movement disorders related to Parkinson’s disease [87]. Overall, a better understanding of inverse agonism at 5-HT 2 receptor systems could have far-reaching implications for the development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that CBD exerts its therapeutic effects through 5-HT 2A receptor activation, as CBD has never been shown to exert psychotropic effects. Thus, involvement of 5-HT 2A in the antipsychotic effect of CBD is unlikely [273].…”
Section: Cbd Receptor Targets In Psychosismentioning
confidence: 99%
“…The FDA subsequently indicated that it will evaluate a new drug application (NDA) from ACADIA on the basis of these two studies and other safety data (65). Preclinical studies indicate that pimavanserin may also be useful for treating the psychosis of Alzheimer's disease (66). Pimavanserin has also been shown to potentiate a subeffective dose of the atypical APD risperidone in acutely psychotic patients with schizophrenia, producing a more rapid onset of action than standard-dose risperidone or an equally effective dose of haloperidol, while producing fewer side effects (67).…”
Section: Treating Parkinson's Disease Psychosis: From Clozapine To Pimentioning
confidence: 99%